2014
DOI: 10.3995/jstroke.36.271
|View full text |Cite
|
Sign up to set email alerts
|

A case of left middle cerebral artery embolism due to Takayasu’s arteritis in the common carotid artery

Abstract: Objective: We report a rare case of left middle cerebral artery embolism due to Takayasu's arteritis in the common carotid artery. Case presentation: A 24-year-old female presented with motor aphasia and right hemiparesis. MRI showed early ischemic changes in the left insular cortex. Cervical MRA showed occlusion of left common carotid artery and left middle cerebral artery (MCA). Because the patient was ineligible for intravenous recombinant tissue plasminogen activator, we chose endovascular therapy for reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Urokinase at 480000 units was intra-arterially injected and aspiration with a Penumbra 3MAX led to recanalization. 5) The other patient had occlusion of the bilateral ICA. Aspiration with a Penumbra for right ICA occlusion led to TICI 2b recanalization, and the use of a stent retriever for left ICA occlusion resulted in TICI 2b recanalization.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Urokinase at 480000 units was intra-arterially injected and aspiration with a Penumbra 3MAX led to recanalization. 5) The other patient had occlusion of the bilateral ICA. Aspiration with a Penumbra for right ICA occlusion led to TICI 2b recanalization, and the use of a stent retriever for left ICA occlusion resulted in TICI 2b recanalization.…”
Section: Discussionmentioning
confidence: 98%
“…3) In Japan, Watanabe et al 4) reported that the incidence was 13.2%, and that embolism was observed in 3.7% of these patients. The pathogenesis of cerebral infarction in the presence of this disease is assumed as follows 5) :…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations